FORMULASI ZAT PENGATUR TUMBUH DENGAN INTERVAL WAKTU SUBKULTUR TERHADAP INISIASI DAN MULTIPLIKASI PISANG TALAS (Musa paradisiaca var sapientum L) SECARA IN VITRO - Rodinah Rodinah; Chatimatun Nisa (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2018)
Talas banana (Musa paradisiaca var sapientum L) is one type of typical bananas in South Kalimantan that has a bright prospect in the future. The plant propagation of talas banana is slower than the other types of bananas. Therefore, it is necessary to use the fast and efficient propagating method, namely by the tissue culture. The growing media used in the banana plant propagation through in vitro culture were Murashige and Skoog media. The propagation of talas banana through in vitro culture used the plant growth regulators of cytokinin, namely BAP, Thidiazuron, and coconut water. The objectives of the research were 1) to find out the PGR formulations in the media of MS and ½ MS with the subculture time interval for optimization of culture products on the initiation and multiplication of the Talas banana’s shoot and root formation called plantlet (Musa paradisiaca var sapientum L). 2) to determine the methods/techniques of in vitro propagation (optimization of each PGR formula on the media of MS and ½ MS with each time interval of Talas banana subculture, the highest number of roots in the treatment of MS + BAP 0.5 mg L-1 while the highest percentage of contamination in MS medium + BAP 0.5 mg L-1.